Compact dual‐band antenna using inverted‐L loop and inner rectangular loop for WLAN applications. Issue 23 (1st November 2015) - Qu, L.; Zhang, R.; Kim, H.H.; Kim, H.
Abstract : A small loop antenna for WLAN applications is proposed, which is comprised of an inverted‐L loop and an inner rectangular loop achieving dual‐band resonances within a compact size of 4.5 mm × 6.5 mm. A series capacitor in the feeding loop is employed for impedance matching of both bands and a shunt capacitor for high band, respectively. The proposed compact antenna is able to achieve −10 dB impedance bandwidth of 120 and 1260 MHz and average radiation efficiency of 69 and 61% in the 2.4 GHz band and the 5 GHz band, respectively.